2013
DOI: 10.1557/opl.2013.996
|View full text |Cite
|
Sign up to set email alerts
|

The Debye Temperature for Hydrothermally Grown ThO2 Single Crystals

Abstract: The electronic properties of ThO 2 single crystals were studied using x-ray photoemission spectroscopy (XPS). The XPS results show that the Th 4f core level is in an oxidation state that is consistent with that expected for Th in ThO 2 . The effective Debye temperature is estimated from the temperature dependent photoemission intensities of the Th 4f core level over the temperature range of 290 to 360 K. A Debye temperature of 468±32 K has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…In Figure a the thorium binding energies (denoted as E F − E ), appear at 334.4 and 343.7 eV for Th 4 f 7/2 and Th 4 f 5/2 , respectively and are consistent with the reported binding energies of refs. . The room temperature uranium binding energies (also denoted as E F − E ) occur at 391.3 and 380.3 eV for U 4 f 7/2 and U 4 f 5/2 , respectively and are consistent with the reported binding energies of 390.8 and 380.8 eV and 390.9 and 380.1 eV …”
supporting
confidence: 85%
“…In Figure a the thorium binding energies (denoted as E F − E ), appear at 334.4 and 343.7 eV for Th 4 f 7/2 and Th 4 f 5/2 , respectively and are consistent with the reported binding energies of refs. . The room temperature uranium binding energies (also denoted as E F − E ) occur at 391.3 and 380.3 eV for U 4 f 7/2 and U 4 f 5/2 , respectively and are consistent with the reported binding energies of 390.8 and 380.8 eV and 390.9 and 380.1 eV …”
supporting
confidence: 85%
“…The crystal structure was confirmed by XRD and then through the rocking curves, oriented in the (200) direction, as found in other Ref. 9–12. Before analysis, the crystals were cleaned using an organic solution of mixed crown ethers and picric acid.…”
Section: Methodsmentioning
confidence: 89%
“…The U 0.22 Th 0.78 O 2 single crystal studied in this research was hydrothermally synthesized kinetically in a supercritical 9 M CsF mineralizer as detailed elsewhere . The structure of U 0.22 Th 0.78 O 2 was confirmed as a fluorite crystal lattice through X‐ray diffraction as previously for other refractory oxides grown through by this method, such as ThO 2 and HfO 2 . The previous studies of ThO 2 obtained through this technique indicated that the surface can have near surface regions of impurity deposits resulting from cooling the hydrothermal solution.…”
Section: Methodsmentioning
confidence: 57%
“…This was followed by the synthesis and structural confirmation of U x Th 1– x O 2 single crystal alloys . While the ThO 2 single crystal band structure has been studied , to our knowledge, the U x Th 1– x O 2 has not been extensively studied beyond colloids, theoretical calculations, or cursory diffraction measurements . Of particular interest is the role of the U 5 f band when included into the ThO 2 matrix.…”
Section: Introductionmentioning
confidence: 99%